Is the blood–brain barrier really disrupted in all glioblastomas? A critical assessment of existing clinical data. Issue 2 (7th September 2017) - Sarkaria, Jann N; Hu, Leland S; Parney, Ian F; Pafundi, Deanna H; Brinkmann, Debra H; Laack, Nadia N; Giannini, Caterina; Burns, Terence C; Kizilbash, Sani H; Laramy, Janice K; Swanson, Kristin R; Kaufmann, Timothy J; et al.
Abstract: The blood–brain barrier (BBB) excludes the vast majority of cancer therapeutics from normal brain. However, the importance of the BBB in limiting drug delivery and efficacy is controversial in high-grade brain tumors, such as glioblastoma (GBM). The accumulation of normally brain impenetrant radiographic contrast material in essentially all GBM has popularized a belief that the BBB is uniformly disrupted in all GBM patients so that consideration of drug distribution across the BBB is not relevant in designing therapies for GBM. However, contrary to this view, overwhelming clinical evidence demonstrates that there is also a clinically significant tumor burden with an intact BBB in all GBM, and there is little doubt that drugs with poor BBB permeability do not provide therapeutically effective drug exposures to this fraction of tumor cells. This review provides an overview of the clinical literature to support a central hypothesis: that all GBM patients have tumor regions with an intact BBB, and cure for GBM will only be possible if these regions of tumor are adequately treated.